On the Boundedness of Solution of the Parabolic Differential Equation with Time Involution - Ashyralyev, Allaberen; Ahmed, Amer (Sulaimani Journal for Pure and Applied Sciences, 2020)
In the present paper, the initial value problem for the parabolic type involutory partial differential equation is investigated. Applying Green’s function of space operator generated by the differential problem, we get formula for solution of this problem. The theorem on the existence and uniqueness of bounded solution of the nonlinear problem with involution is established.
Keywords: Hilbert space; Boundedness; Involution; Parabolic equation